2001
DOI: 10.2527/2001.7992276x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of several supplementation frequencies on forage use and the performance of beef cattle consuming dormant tallgrass prairie forage.

Abstract: Two experiments were conducted to quantify the impact on forage use and performance of varying supplementation frequency of cattle consuming forage diets across a range of frequencies. In both experiments, a common supplement was used that contained a relatively high concentration of CP (43%) and was fed at the following frequencies: 1) 2 d/wk; 2) 3 d/wk; 3) 5 d/wk; and 4) 7 d/wk. In Exp. 1, 120 Hereford x Angus cows (BW = 537 kg) grazing winter tallgrass-prairie range were supplemented at the various frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 14 publications
6
23
1
2
Order By: Relevance
“…In contrast, Farmer et al (2001) provided degradableintake protein supplement 7x, 5x, 3x or 2x per week and reported that fluid passage rate responded quadratically, with the lowest rate occurring on the supplementation provided 2x per week. The infrequent supplementation of degradable-intake protein may have disrupted rumen function for a period of time, especially in the lower supplementation frequency (Bohnert et al, 2002c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Farmer et al (2001) provided degradableintake protein supplement 7x, 5x, 3x or 2x per week and reported that fluid passage rate responded quadratically, with the lowest rate occurring on the supplementation provided 2x per week. The infrequent supplementation of degradable-intake protein may have disrupted rumen function for a period of time, especially in the lower supplementation frequency (Bohnert et al, 2002c).…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation frequency had little or no effect on VFA concentrations in comparison with daily supplementation. Similarly, other authors (Farmer et al, 2001;Currier et al, 2004;and Morais et al, 2009) have reported that two-day supplementation intervals (or shorter) had some or no effect on VFA. Morais et al (2009) observed that ruminal fermentation parameters (pH, NH 3 -N and VFA) in Nellore steers on Brachiaria brizantha pastures were stable when supplementation was reduced from seven to five or three times per week; they concluded that the maintenance of these parameters was important for adequate ruminal fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Köster et al (2002) indicated that inclusion of urea in supplements at less than 45% of DIP would not significantly depress performance of prepartum cows grazing dormant tall grass prairie in Kansas. Others (Beaty et al, 1994;Farmer et al, 2001) observed that infrequent (i.e., 2 to 3 times/wk vs. daily) DIP supplementation can be practiced without greatly affecting performance outcomes of winter grazing beef cows. Farmer et al (2004b) found that inclusion of NPN (30% or less of DIP concentrations) in protein supplements fed on alternative days to beef cows grazing dormant tallgrass prairie did not compromise beef cow performance.…”
Section: Degradable and Undegradable Intake Proteinmentioning
confidence: 99%
“…Supplemental feeds may constitute a significant portion of variable costs of beef production, and providing protein supplements less frequently may reduce costs without negatively affecting performance (Huston et al, 1999;Farmer et al, 2001;Bohnert et al, 2002).…”
Section: Introductionmentioning
confidence: 99%